Methamphetamine Use, Syphilis, and Specific Online Sex Partner Meeting Venues Are Associated With HIV Status Among Urban Black Gay and Bisexual Men Who Have Sex Men. (August 2021) - Jennings, Jacky M.; Wagner, Jessica; Tilchin, Carla; Schumacher, Christina M.; Thornton, Nicole; Hamill, Matthew M.; Rompalo, Anne; Ruhs, Sebastian; Rives, Sarah; Ghanem, Khalil G.; Latkin, Carl
Abstract : Background: In the context of increasing syphilis rates, particularly among Black men who have sex men (MSM), the objectives were to determine the associations between methamphetamine (meth) use and syphilis and HIV positivity, and to identify sex partner meeting venues as potential intervention access points among Black MSM in a mid-Atlantic US city. Methods: This study is an ongoing longitudinal cohort study. Participants were recruited from clinical and nonclinical settings and included sexually active MSM aged 18 to 45 years. The baseline visit included a behavioral survey and testing for syphilis, HIV, gonorrhea, and chlamydia. Logistic regression analyses were used for hypothesis testing. Results: Among 359 MSM completing baseline, 74.4% (268) Black MSM were included; 31% (84) were aged 24 to 29 years, 43.7% (117) reported unprotected anal intercourse at last sex, and 15.3% (41) reported meth use in the past 3 months. Sixteen percent (43) had syphilis, 46.6% (125) were living with HIV, and 19.0% (51) had gonorrhea and/or chlamydia. Meth use was associated with sexual and drug risk behaviors and HIV, but not syphilis. In adjusted analyses, meth use increased the odds of HIV positivity by 6.43 (95% confidence interval, 2.30–17.98) and syphilis positivity by 2.57 (95% confidence interval, 1.23–5.37). Four online sex partner meeting venues were associated with meth use and HIV, whereas syphilis was associated with one. Conclusions: Among Black MSM, meth use and syphilis positivity were associated with more than 6-fold and almost 3-fold increased adjusted odds of HIV positivity, respectively. Four specific sex partner meeting venues may be important access points for HIV/sexually transmitted infection and substance use prevention. Abstract : A study among urban Black men who have sex men found that methamphetamine use and syphilis positivity were associated with HIV positivity, and specific sex partner meeting venues may provide intervention access points.Supplemental digital content is available in the text.